Corporate governance in Islam VIS-A-VIS the modern corporate world / M. M. Sulphey - Sulphey, M. M. (Accounting Research Institute (ARI) & Faculty of Accountancy, 2015)
The concept of corporate governance (CG) has gained critical interest and has become a debating point since the mid-1980s. It became an aspect of concern when the corporate world became aware of the importance of protecting the rights of all stakeholders. Islam calls for an effective combination of the rules pertaining to Tawhid and SharVah in the day-to-day life of Muslims in general and in business in particular. This study presents a basic understanding of Islamic CG and compares the Islamic concept of CG vis-a-vis the Organization for Economic Cooperation and Development principles.